Testicular tumors - Giovanni Rosti; Ornella Carminati; Claudia Casanova; Giorgio Papiani (Frontiers Media S.A., 2011)
Germ cell tumors of the testes represent a unique paradigm of diseases which can be cured even in extremely advanced phase. Unfortunately, this makes them unique among adult solid tumors. Seminoma and non seminoma are relatively rare with approximatively 25,000 patients in Europe per year, but numbers are increasing world wide. Different strategies are needed depending on stage and prognostic scores. Seminoma is extremely sensitive to radiation therapy and chemotherapy, while all germ cell tumors show a very good response to chemotherapy. Clinical stage I seminoma is currently treated with radiation, single course carboplatin or surveillance policy. Clinical stage I non seminoma can also be approached with different strategies such as retroperitoneal lymph node dissection, observation or one-two courses of standard chemotherapy. Stage II seminoma may be treated with either radiation or chemotherapy, while for all advanced stages chemotherapy is mandatory. Since the mid-eighties PEB (Cisplatin, Etoposide and Bleomycin) is the regimen of choice and no other schedule has proved superior in terms of efficacy. Surgery on the residual disease is crucial to the whole strategy and should be performed or attempted in all cases. Consequently, the correct treatment strategy for these tumors does not depend only on the ability of a single physician, but on a skilled team specialized in this particular tumor. Second line therapies (VeIP, PEI, TIP) can cure 25%-40% of patients, but improved strategies for resistant tumors are desperately needed. High-dose chemotherapy has shown very good results in some studies while being less impressive in others. In any case, it should remain an option for relapsing patients and could be used in some cases of upfront chemotherapy in patients with slow marker decline, but this should only be considered in referring centers.